Europe in the long twentieth century a transnational history - Cornelißen, Christoph 1958- (Oxford University Press, 2024)
Tracing Europe in the long 20th century as it moved from a leading world region to a group of states constantly trying to assert themselves globally, this volume examines the tension between national and imperial ambition, competition between political orders, the transformation of economy and society, and the impact of ideas and utopias.